Assessing Public Investment Management Functions and Institutional Arrangements for State-Owned Enterprises : A Diagnostic Framework - Glenday, Graham; Le, Tuan Minh; Mahdi, Shireen; Pijuan, Albert (World Bank, Washington, DC, 2021)
This paper provides a diagnostic framework (DF) for helping governments conceptualize and develop desirable functions and institutional arrangements for public investments managed by state-owned enterprises (SOEs). The DF also extends its coverage to not-for-profit, quasi-independent government entities. Determining the appropriate approach to managing SOE public investments requires a measured reconciliation of multiple trade-offs. In certain cases, when SOEs make profit-seeking investments for commercial purposes, operate in competitive markets, and make investments that present no major externalities, governments should take a hands-off approach, a scenario that may include cases in which governments simply exit and leave the corporate governance in the hands of private investors. Governments should let SOEs make their own investment decisions in pursuit of business efficiency. In such instances, governments need to establish a level playing field on which SOEs can operate and compete with private actors and exercise their public interest as a shareholder. In other cases, however, governments should establish a robust system - well aligned with the national public investment management (PIM) architecture to regulate SOE investments. This alignment should occur when SOE investments extend the role of line ministries and are financed by the general government budget or involve large-scale projects, posing significant fiscal risks through implicit or explicit contingent liabilities. The PIM practiced by SOEs should also align with the national PIM system when there are potential detrimental impacts on the environment, climate, and resilience. Our DF consists of four matrices intended to be used in combination to assess the gap between a country’s current SOE PIM and international best practices. Matrix 1 sketches the guideposts to determine which stakeholders should guard SOE investments, focusing on who. Matrix 2 helps assess PIM functions, focusing on what should be done under each PIM function and by whom. Matrix 3 presents a framework and a set of measurement indicators to evaluate how governments should introduce PIM processes and systems. Matrix 4 gives some consideration to the project viability of SOEs. To effectively apply the DF, it cannot be used mechanically: it must be grounded in a good understanding of the country’s political economy and the vested incentives of all stakeholders involved in SOE PIM.